Bart H.

asked • 02/03/21# Calculus 1 Question Derivatives

1)Assume that *g*(*y*) has a derivative at *y *= 3.5 with *g*′(−3.5) = −3. Using the definition of the derivative, explain why the function *f *(*y*) = *g*(*y*) − 10 has a derivative at *y *= 3.5 with

*f*′(3.5)=−3.

2)Assume that *g*(*y*) has a derivative at *y *= 3.5 with *g*′(−3.5) = −3. Use geometry to explain why the function *f *(*y*) = *g*(*y*) − 10 has a derivative at *y *= 3.5 with *f *′(3.5) = −3.

## 1 Expert Answer

The - part of the -3.5 is a typo. For 1, use the limit definition of derivative at a pt: f'(a) = lim_{x→a} (f(x)-f(a))/(x-a) :

f(y) = g(y) - 10. , f(3.5) = g(3.5) - 10

g'(3.5) = lim_{y→3.5} (g(y) - g(3.5)) / (y - 3.5) = - 3

f'(3.5) = lim_{y→3.5} (f(y) - f(3.5)) / (y - 3.5) = (g(y) - 10 - (g(3.5) - 10))/ (y - 3.5) = (g(y) - g(3.5)) / (y - 3.5) = - 3 ◊

2) The graph of f(y) is the graph of g(y) shifted down 10, which will not alter its shape (rate of change). The tangent to f's curve at y = 3.5 will have the same slope as the tangent to g's curve at y = 3.5.

## Still looking for help? Get the right answer, fast.

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.

William W.

Are you sure it's supposed to say g'(-3.5) as opposed to g'(3.5)?02/03/21